(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: It is demonstrated that students with better emotional intelligence (EI) had better self-esteem. The aim of study was to assess the role of self-esteem in the relationship of EI and LS. Methods: This cross-sectional study was done on 403 students of Shahroud University of medical sciences (northeast of Iran). In this study we used Schering Emotional Intelligence Questionnaire and Diener Satisfaction Questionnaire and Cooper Smith Self-Esteem Questionnaire. Mediation analyzes was done to assess the role of SE in the relationship of EI and LS. Results: About 82% of students had high emotional intelligence level. Comparison of the mean scores of EI, SE and LS by sex showed that there was no significant difference between gender means. The mean score of LS in the groups with high and moderate levels of EI score showed a significant difference between the life satisfaction score between two groups. The results of the mediation analysis showed that SE has a mediatorial role in the relationship between EI and LS, as 98% of the effect of emotional intelligence relationship is through mediating role of self-esteem. Conclusions: Self-esteem showed as an important mediator in the relationship of EI and LS. Regarding this valuable finding, better EI which results in better self-esteem and life satisfaction and these three items could separately results in a series of good results. Keywords: Self-Esteem, Life Satisfaction, Emotional Intelligence.